Pemilihan Bahasa Arab dalam Pengantar Dakwah pada Komunitas Yayasan Amanisya Qur’an Learning - Malida, Alya (Research Community for Critical Society and Environment, 2025)
Language selection in the context of preaching is a complex phenomenon and important to understand in religious communication. This study aims to reveal the patterns of language selection that occur in the Amanisya Qur'an Learning (AQL) Foundation community, as well as the factors that influence it. The research method used is a qualitative study with a sociolinguistic approach. Data were collected through participant observation. Data analysis was carried out in three stages, namely (1) data reduction, (2) data presentation, and (3) conclusion. The study's results showed variations in language selection between various interaction contexts, such as preaching assemblies and teaching the Qur'an. This study's results indicate that two dominant codes are used in the community, namely the Indonesian and Arabic codes. From the speech found, there is a phenomenon of code-switching and code-mixing between the Indonesian (BI), Arabic (BA), and English (BING) codes. Moreover, the factors that influence language selection are (1) participants, (2) situations, (3) speech content, and (4) interaction functions. These findings provide better insight into the dynamics of communication in da'wah and can be a basis for developing more effective communication strategies in da'wah activities in society.